Op weg na ’n menswaardige samelewing? Die rol van teorievorming en wetgewing. - Katts, DJ; Koopman, NN (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
On the way to a society of human dignity? The role of theory-formation and lawmaking. The Bill of Rights of the South African Constitution of 1996 envisages a society of human dignity, both in its preamble and in article 10. The logic seems to be that the fulfilment of human rights will imply the actualisation of a society of dignity. This paper investigates the role that both theory-formation about the implementation of human rights and lawmaking processes that enhance the implementation of human rights, can play in the realisation of a society of human dignity.